2018
DOI: 10.1080/17843286.2018.1474614
|View full text |Cite
|
Sign up to set email alerts
|

Lemierre’s syndrome: a case study with a short review of literature

Abstract: Objective and Importance Lemierre's syndrome (LS) is a rare condition that typically starts with a bacterial oropharyngeal infection complicated by a thrombophlebitis of the internal jugular vein and septic emboli to the lungs or other organs. The most common organism isolated is Fusobacterium necrophorum, although other causative organisms are isolated in rare cases. Case presentation We discuss a case of LS in a 44-year-old, previously healthy man presenting with an oropharyngeal infection. F. necrophorum wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
10
0
10
Order By: Relevance
“…This is consistent with other studies which have shown F. Necrophorum is most susceptible to antibiotics such as metronidazole, clindamycin, and beta-lactams due to good penetration and oral bioavailability. [3] , [14] Studies maintain that clinicians should begin treatment with broad-spectrum therapy with anerobic coverage. [15] Conversely, anticoagulative therapy was only used in 35 cases, half of the cases analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies which have shown F. Necrophorum is most susceptible to antibiotics such as metronidazole, clindamycin, and beta-lactams due to good penetration and oral bioavailability. [3] , [14] Studies maintain that clinicians should begin treatment with broad-spectrum therapy with anerobic coverage. [15] Conversely, anticoagulative therapy was only used in 35 cases, half of the cases analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Tanto la ligadura como la resección de la vena trombosada era una práctica habitual en la era preantibiótica. Hoy día no se utiliza o se reserva para los casos de sepsis no controlada con tratamiento convencional o persistencia de embolias sépticas a pesar de un adecuado tratamiento antibiótico (6,7,(10)(11)(12)(15)(16)(17) .…”
Section: Discussionunclassified
“…It is still a rare syndrome with an estimated worldwide incidence of 1/1,000,000 [6]. F. necrophorum is a gram-negative, non-spore forming, anaerobic bacilli [1]. F. necrophorum is divided into two subspecies: F. necrophorum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…It is not recommended in the absence of thrombus extension [9]. Anticoagulation should be considered on an individual basis with specialist teams involved if there is evidence of significant extension of thrombus, especially in the presence of persistent, progressive or refractory bacteremia or uncontrolled clinical sepsis [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation